Indigenisation and history: how opera in South Africa became South African opera - Roos, Hilde (University of the Free State, 2012)
In South Africa, the exposure of opera to local cultures and circumstances has in time resulted in a number of opera productions that have departed from Western aesthetic norms and prompted innovations to the genre. These innovations can be traced in newly created operas as well as in the production of a number of operas from the standard canon that have been ‘translated’ to local contexts and social realities. This article explores the historical trajectory of opera production in South Africa from 1801 to the present through the lens of indigenisation and shows that, in its most subtle form, this phenomenon can be traced in local opera productions long before the issue of the reflection of indigenous cultures in opera became relevant. In constructing this history, the author hopes to identify moments when one musical element became another, or changed sufficiently to become a similar, but different element. Clearly, in discovering the South African roots of opera and understanding the many projects that currently characterise the opera scene in this country, the issue is not only one for cultural or textual analysis, but also, very pertinently, a matter for historiography.

inheemse kulture het mettertyd ’n verskeidenheid operaproduksies laat ontstaan wat afwyk van Westerse estetiese norme en wat vernuwing tot gevolg gehad het. Hierdie vernuwings kan gevind word in nuut-gekomponeerde operas, maar ook in die her-interpretasie van operas van die bestaande kanon binne plaaslike kontekste en sosiale werklikhede. Hierdie artikel volg die historiese trajek van operaproduksie in Suid-Afrika deur die lens van verinheemsing vanaf 1801 tot vandag, en toon aan dat verinheemsing in plaaslike produksies opgespoor kan word lank voor die verteenwoordiging van inheemse kulture in opera relevant begin word het. Deur die konstruksie van ‘n geskiedenis van opera bly die skrywer sensitief vir die momente wanneer elemente van operaproduksie getransformeer of aangepas is terwyl die oorspronklike formaat steeds herkenbaar bly. Die ontdekking van die plaaslike wortels van die genre van opera en die ontwikkeling van ’n begrip vir die uiteenlopende gedaantes van huidige Suid-Afrikaanse operaproduksie is nie slegs ’n kwessie vir kulturele of tekstuele analise nie; dit is pertinent ook een vir historiografie.
Keywords: South Africa; Indigenisation; History; Opera; Historiography